Fortification of the Border with Albania in the Zeta Division Area - Velojić, Dalibor Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The border front in the Zeta division area was determined in accordance with thorough measures regarding fortification of the border with Albania. Although the plan of military operations predicted the offensive in this direction, i.e., the preventive strike in the Albanian territory, the activity was terminated by the main operator no. 6 from the headquarters of the 3rd Army division. This misunderstanding was the result of vague orders of the Ministry of the Army and the Navy, which, being responsible for the fortification also appointed the officers from the headquarters of the Zeta division for this activity. This inconsistency in turn led to delay, and this direction was fortified only in part.
Keywords: Yugoslav Army; Zeta division; fortification; Albania